Globalização e ambientalismo: etnicidades polifônicas na Amazônia Globalization and environmentalism: polyphonic ethnicities in the Amazon - Luiza Garnelo; Sully Sampaio (História, Ciências, Saúde: Manguinhos)
O texto problematiza a globalização, suas contradições e os modos como ela orienta e configura as situações específicas encontradas na realidade amazônica atual, produzindo simultaneamente uma uniformização da produção econômica e a valorização das diferenças culturais. A discussão explora as nuanças da instalação de uma base produtiva massificada e padronizada que, paradoxalmente, promove a valorização das diferenças culturais, favorecendo alianças entre lideranças etnopolíticas de grupos indígenas amazônicos, de um lado, e ambientalistas e outros atores trans-mundiais de forte poder decisório, de outro. O texto analisa a rede de alianças do movimento indígena, enfatizando a polifonia dos diversos agentes políticos que se conflagram nesse cenário geopolítico contemporâneo. The article examines the issue of globalization, along with its contradictions and the ways in which it guides and shapes specific situations within the Amazon's present-day reality, while simultaneously engendering the uniformization of economic production and the valorization of cultural differences. The discussion explores the nuances of implementing a massified, standardized productive base that paradoxically fosters the valorization of cultural differences and favors alliances between, on the one hand, ethno-political leaders from indigenous Amazon groups and, on the other, environmentalists and other transworld actors who wield strong decision-making power. The article analyzes the indigenous movement's network of alliances and highlights the polyphony of the different political agents that come to clash with each other within this post-modern geopolitical setting.